Subthreshold membrane potential oscillations in inferior olive neurons are dynamically regulated by P/Q- and T-type calcium channels: a study in mutant mice - Choi, Soonwook; Yu, Eunah; Kim, Daesoo; Urbano, Francisco J.; Makarenko, Vladimir; Shin, Hee-Sup; Llinas, Rodolfo R. (WILEY, 2010)
The role of P/Q- and T-type calcium channels in the rhythmic oscillatory behaviour of inferior olive (IO) neurons was investigated in mutant mice. Mice lacking either the Ca(V)2.1 gene of the pore-forming alpha 1A subunit for P/Q-type calcium channel, or the Ca(V)3.1 gene of the pore-forming alpha 1G subunit for T-type calcium channel were used. In vitro intracellular recording from IO neurons reveals that the amplitude and frequency of sinusoidal subthreshold oscillations (SSTOs) were reduced in the Ca(V)2.1-/- mice. In the Ca(V)3.1-/- mice, IO neurons also showed altered patterns of SSTOs and the probability of SSTO generation was significantly lower (15%, 5 of 34 neurons) than that of wild-type (78%, 31 of 40 neurons) or Ca(V)2.1-/- mice (73%, 22 of 30 neurons). In addition, the low-threshold calcium spike and the sustained endogenous oscillation following rebound potentials were absent in IO neurons from Ca(V)3.1-/- mice. Moreover, the phase-reset dynamics of oscillatory properties of single neurons and neuronal clusters in IO were remarkably altered in both Ca(V)2.1-/- and Ca(V)3.1-/- mice. These results suggest that both alpha 1A P/Q- and alpha 1G T-type calcium channels are required for the dynamic control of neuronal oscillations in the IO. These findings were supported by results from a mathematical IO neuronal model that incorporated T and P/Q channel kinetics.
Keywords: IN-VITRO; STOCHASTIC RESONANCE; CEREBELLAR; CAT; COMMUNICATION; INFORMATION; MODULATION; BEHAVIOR; NUCLEUS; BIOLOGY